Mother’s level of education and attitude determines the provision of complete basic immunization in infants - Rahmadani, Risna Ayu; Lumintang, Yuliati; Chabibah, Ike FA (Jurnal Ilmiah Kesehatan Sandi Husada, 2025)
Introduction: Immunization is an effort to introduce vaccines into the body to increase a person's immunity to prevent a disease. The impact or risk that occurs due to incomplete immunization is that children are more susceptible to illness, are at more risk of infecting family members or the environments, and the quality and life expectancy decrease. During the research, data was found that 19 out of 35 infants did not receive complete immunization. The purpose of this research was to find out the relationship between the mother’s level of education and attitude towards the provision of complete basic immunization in infants at the Tombatu Community Health Center, Winorangian Satu Village. Methods: Partial analytical observational research with a cross-sectional design with independent variables and dependent variables conducted once at the same time with a sample size of 35 respondents. The analysis method used is Chi square. Result: The mother's education level was higher in the high category (>junior high school) and the mother's attitude with a frequency of 19 respondents (not supporting <50%). The results of the Chi square test showed that there was a relationship between maternal education level and the provision of complete basic immunization in infants at the Tombatu Community Health Center, Winorangian One Village, p-value = 0.00. The results of the Chi square test showed that there was a relationship between maternal attitudes and the provision of complete basic immunization in infants at the Tombatu Community Health Center, Winorangian Village. One p-value = 0.00. Conclusion: From the results of the study was found that there is a relationship between the mother’s level of education and the provision of complete basic immunization to babies at the Tombatu Community Health Center. Winorangian Satu Village and there is a relationship between the mother's attitude and the provision of complete basic immunization in infants at the Tombatu Community Health Center, Winorangian Satu Village.